The metropolis in Latin America, 1830-1930 : cityscapes, photographs, debates. - Alonso, Idurre; Getty Research Institute; Casciato, Maristella (Los Angeles : Getty Research Institute, 2021)
"The Metropolis in Latin America, 1830-1930: Cityscapes, Photographs, Debates examines the unprecedented growth of several cities from 1830 to 1930, observing how sociopolitical changes and upheavals created the conditions for the birth of the metropolis"--
Chronology of Events in Latin America, 1800- -- Chart of Population Growth in Latin American Metropolises and Los Angeles, 1800- -- Introduction / Idurre Alonso and Maristella Casciato -- Album: Capital Cities -- The Emergence of Capital Cities in Nineteenth-Century Latin America / Germán Rodrigo Mejía Pavony -- Order, Nature, and Society: Exile and Return from Paradise in the City to Come / Jorge F. Rivas Pérez -- Album: Colonial Cities and National Heroes -- From Postcolonial Cities to the First Metropolises in Latin America / Arturo Almandoz -- The Domination of Nature in the Construction of the Urban Landscape / Sonia Berjman -- Album: Leisure -- The Visible and the Invisible: The Photographic Image of the Metropolis / Idurre Alonso -- Visions of Mobility: Early Cinema Reaching Capital Cities in Latin America / David M.J. Wood -- Album: Infrastructures -- Shaping the Metropolis: Urban Plans for Rio de Janeiro and Buenos Aires / Maria Cristina da Silva Leme -- The Resurgence of the Ancient Past: Mexico City in the Age of Modern Technologies / Cristóbal Jácome-Moreno -- The Search for a New Art: Pre-Hispanic and Colonial Reinterpretations in the Americas / Rodrigo Gutiérrez Viñuales -- Album: Debates -- Architects and Urban Planners: Transatlantic Journeys from Europe to Latin America / Maristella Casciato -- Album: Toward Modernism.
boek
Keywords: Urbanization -- Latin America -- History; Cities and towns -- Latin America -- History; City planning -- Latin America -- History